Tratamento do resíduo da depuração (UKP) da indústria de celulose para produção de chapas minerais - César, Antônia Amanda da Silva (2015)
The production process of cellulose generates many residues, among which are the fibers resulting of cleansing. The employment of these residues in product manufacturing can add value and solve environmental issues, in addition to contributing for developing new products and technologies. The objective of this work was to characterize the UKP (Unbleach Kraft Pulp) residue, using it to produce and characterize wood-cement panels. The residue was evaluated under the following conditions: in natura (N), with water immersion for 24 hours (A), with immersion in 10% sodium hydroxide for 24 hours (H), and with immersion in both liquids with subsequent material refining (RA and RH). We evaluated the residue‟s anatomical traits, chemical composition, behavior to thermal decomposition, particle size distribution and basic and bulk densities. The mineral panels were produced with nominal density of 1.4 g.cm-3 , and the following pressing cycle: ambient temperature, pressure of 04 MPa and stapling for 24 hours. Subsequently, the panels were acclimatized and cut into proofbodies for conducting the following physical and mechanical tests: water absorption after 2 and 24 hours of immersion, thickness swelling after 2 and 24 hours of immersion, apparent density, thickness non-return rate, moisture, screw holding, compression, internal bonding and static bending. For particle distribution, the highest percentage of material was retained in the 20 mesh sieve. For the anatomical traits, there was decrease in the length of the fibers and in the thickness of the fiber wall for treatments undergoing refinement. For chemical constitution, there was decrease in the percentage of lignin and extractives for treatments with refinement and hydroxide. Concerning the behavior of the residue in function of thermal decomposition, the curves commonly found for wood and lignin-cellulose residues were similar, differing only at the point of lignin decomposition. Regarding the evaluated physical properties, there was no significant difference between treatments for the following variables: D (1.41 g.cm-3 ), UM (9.9%) and TNR (0.9%). For variables AA_2h, AA_24h, IE_2h, IE_24h, LI, AP, CP, MOE and MOR there were significant differences between the proposed treatments. In general, the treatments with immersion in hydroxide and those with refining presented better performance. Therefore, we can infer that this is a promising destination for the residue, however requiring more research.